Sustainability Analysis of Lemuru (Sardinella lemuru) Commodity Resources in Bali Strait - Finuricha Yoana Putri; Andi Kurniawan; Rita Parmawati (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Potential of resource commodities contained in the waters of the Bali Strait needs to be studied for the level of utilization and the level of sustainability. This research aimed to analyze the conditions for the utilization of lemuru fish resources commodities and the sustainability status of lemuru fisheries in the Bali Strait based on four aspects, namely ecological, economic, social, and technological dimensions. Commodity condition of resources is carried out with Catch Per Unit Effort (CPUE) analysis, while the sustainability status of resource commodities uses Rappid Appraisal for Fisheries (RAPFISH) analysis. Data used in this study is based on data from PPN Pengambengan, Bali and PPP Muncar, Banyuwangi. The questionnaire was distributed to 55 respondents with purposive sampling techniques. The results of the analysis on the CPUE of the commodity condition of lemuru fish resources in 2013-2017 experienced a decrease and the occurrence of over-fishing in the Bali Strait. Meanwhile, based on the status of sustainability, it shows that the status is less sustainable in a multidimensional manner with a value of 36.47.